2016
DOI: 10.1002/cphc.201501163
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c‐Capped Fluorescent Gold Nanoclusters: Imaging of Live Cells and Delivery of Cytochrome c

Abstract: Cytochrome c-capped fluorescent gold nanoclusters (Au-NCs) are used for imaging of live lung and breast cells. Delivery of cytochrome c inside the cells is confirmed by covalently attaching a fluorophore (Alexa Fluor 594) to cytochrome c-capped Au-NCs and observing fluorescence from Alexa 594 inside the cell. Mass spectrometry studies suggest that in bulk water, addition of glutathione (GSH) to cytochrome c-capped Au-NCs results in the formation of glutathione-capped Au-NCs and free apo-cytochrome c. Thus glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
(179 reference statements)
0
17
0
Order By: Relevance
“…Cytochrome c coated gold nanoclusters were prepared following our previously reported method. 19 2.2c FCS data measurement and analysis: Our experimental setup for FCS and collection of FCS data are described in detail in our earlier publication. 28 Tween-20 (0.005%) was used to prevent attachment of the protein coated nanoclusters to the glass surface of the cover slip during the experiment.…”
Section: 2b Gold Nano-cluster Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytochrome c coated gold nanoclusters were prepared following our previously reported method. 19 2.2c FCS data measurement and analysis: Our experimental setup for FCS and collection of FCS data are described in detail in our earlier publication. 28 Tween-20 (0.005%) was used to prevent attachment of the protein coated nanoclusters to the glass surface of the cover slip during the experiment.…”
Section: 2b Gold Nano-cluster Preparationmentioning
confidence: 99%
“…14,18 20 Recently, we have used cytochrome c-protected gold nano-cluster (AuNC) to deliver cytochrome c (Cyt C) inside live cells. 19 Also, we have used lysozyme-protected AuNC for selective delivery of an anti-cancer drug to breast cancer cell without affecting normal breast cells. 14 This led to selective killing of the breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The gold nanoclusters (AuNCs) have been attracted an immense interest across the globe since last two decades for the synthesis and wide range of applications including sensing, imaging, and therapy due to their very small size (∼2 nm) and bio‐inertness . In addition to their fundamental importance (connecting link between atoms and nanoparticles), they have outstanding optical properties such as wide range of luminescence (from UV to NIR), and large Stokes shift.…”
Section: Antibacterial Gold Nanoclustersmentioning
confidence: 99%
“…42 Bhattacharyya and co-workers also tried to induce apoptosis in cells by delivering the protein cytochrome C through AuNCs in lung and breast cells. 41 They have demonstrated that the addition of GSH releases the protein and the AuNCs subsequently gets capped by the GSH instead. Unfortunately, this strategy killed non-cancer cells more effectively than cancer cells.…”
Section: ¹1mentioning
confidence: 99%
“…40,42 When protected by 2-(naphthalen-2-yl) ethane-thiolate ligand, the Au 25 NCs displays a much higher quantum yield and a different lifetime than when using 2-phenylethanethiolate as the protecting ligand. 41 The enzymatic photo-catalytic reduction of oxygen has been demonstrated to be enhanced by Martinez and co-workers using AuNCs templated by a hybrid DNA. 43 Pradeep and co-workers demonstrated that near-infrared (NIR) luminescent AuNCs can be generated through a protein (bovine serum albumin)-bound Au + intermediate.…”
mentioning
confidence: 99%